The Influence of Service Innovation and Physical Work Environment on Public Satisfaction Mediated by Public Service Performance at the Regional Revenue Agency of West Tanjung Jabung Regency - Andreas Sinaga; Fakhrul Rozi Yamali; Mufidah Mufidah (Dinasti Publisher, 2026)
This study aims to describe service innovation, physical work environment, service performance, and public satisfaction at the Regional Revenue Agency (Bapenda) of West Tanjung Jabung Regency (Tanjabbar), and to analyze the influence of service innovation and physical work environment through service performance on public satisfaction. This study is supported by several theories related to the research variables. This study was conducted at the Regional Revenue Agency of West Tanjung Jabung Regency. With a population of 120,740 people, while the sample size in this study uses Slovin's theory with a margin of error of 10% so that 100 people are obtained. This study uses a quantitative approach with a survey method and uses Partial Least Square (PLS) data analysis. The results show that service innovation and physical work environment have an influence on public satisfaction, both directly and indirectly through service performance at the Regional Revenue Agency of West Tanjung Jabung Regency. This finding indicates that the positive influence of service innovation and physical work environment on public satisfaction does not occur directly, but is carried out (mediated) through improved service performance.